Factors Related to Antenatal Care Visits in Seba Primary Health Center, District Sabu Raijua - Djami, Ari Yantievada Ratu; Littik, Serlie K; Sinaga, Masrida (Faculty of Public Health, Nusa Cendana University, 2023)
The Maternal Mortality Rate (MMR) has increased from 2019 to 2021. Antenatal Care is one of the efforts to reduce MMR. The K4 coverage of the Puskesmas Seba in 2019–2021 fluctuated and tended to decrease, so that it had not been able to meet the target of minimum service standards for pregnant women visits of 85%. The purpose of this study was to identify the factors associated with antenatal care visits for mothers in the working area of ​​the Puskesmas Seba in 2022. This research was conducted in the form of an analytic survey with a cross-sectional design. The research sample consisted of 372 research participants, which included 77 respondents. The questionnaire instrument was used together with the interview method to obtain data. Descriptive analysis and Spearman's test with α=0.05 were used to process the data. The test results showed that antenatal care visits were related to knowledge (p = 0.000), perceived suscepibility (p = 0.004), perceived benefits (0.004), and perceived barrier (0.000). Age (p=0.163) and husband's support (p=0.056) were not related to antenatal care visits. The test results also show a fairly strong relationship between the variables of knowledge, perceived suscepibility and perceived benefits, while there is a very strong correlation between perceived barriers and antenatal care visits. The recommendation that can be given is that health workers can offer more counseling and counseling to mothers so that they will be more motivated to make visits.